2012
DOI: 10.4103/0253-7613.93856
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three a-priori models in the prediction of serum lithium concentration

Abstract: Context:Mathematical models are valuable for optimizing drug dose and dosing regimens.Aims:To compare the precision and bias of three a-priori methods in the prediction of serum level of lithium in patients with bipolar disorder, and to determine their sensitivity and specificity in detecting serum lithium levels outside the therapeutic range.Settings and Design:Hospital-based, retrospective study.Materials and Methods:In a retrospective study of 31 in-patients, the serum level of lithium was calculated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…To address these issues, several strategies for predicting serum lithium concentrations from oral doses, which are classified into 2 categories (i. e., a prior predictive method and test-dose method), have been proposed [5]. However, the root mean squared prediction error, which is a proxy for accuracy of prediction with a higher value indicating lower prediction performance, was reported to be as high as 0.37, 0.59, and 0.57 mmol/L in the prediction models by Pepin et al [6], Zetin et al [7], and Abou Auda et al [8], respectively [9]. This insufficient predictive power of those prediction models hampers the use of them in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, several strategies for predicting serum lithium concentrations from oral doses, which are classified into 2 categories (i. e., a prior predictive method and test-dose method), have been proposed [5]. However, the root mean squared prediction error, which is a proxy for accuracy of prediction with a higher value indicating lower prediction performance, was reported to be as high as 0.37, 0.59, and 0.57 mmol/L in the prediction models by Pepin et al [6], Zetin et al [7], and Abou Auda et al [8], respectively [9]. This insufficient predictive power of those prediction models hampers the use of them in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…5 The Pepin et al 6 and Jermain et al 12 equations make multiple assumptions regarding clearance, elimination halflife, and volume of distribution. [5][6][7][8][9] These assumptions may increase the potential for error in each equation.…”
Section: Discussionmentioning
confidence: 99%
“…Pepin and colleagues initially developed an equation based on first-order, one-compartment, patient-specific pharmacokinetic parameters that have been evaluated in several small studies. [5][6][7][8][9] The complex computation required by this equation may limit its utility. Zetin et al 2 similarly developed an equation based on patient-specific parameters using multiple linear regression analysis for derivation 2,5,[7][8][9][10][11] ; however, the authors potentially omitted an influential variable.…”
mentioning
confidence: 99%
“…In addition, they reported that the calculation of Li-CL and estimation of lithium dosage using their method was more reliable compared to the Jermain, Pepin and Terao methods [19]. Moreover, Radhakrishnan et al compared the Pepin, Jermain and Abou-Auda methods for Css prediction, and reported that the Pepin method was the most precise, where as the Abou-Auda method was the least biased [20].…”
Section: Citationmentioning
confidence: 99%
“…However, this consideration may be negligible in the population of the present study, due to good adherence to therapy schedules as well as generally stable condition of their disease. [6,14,[20][21][22], standardized prediction methods using Li-CL and Css remain to be elucidated.…”
Section: Citationmentioning
confidence: 99%